Intestinal Microbiota as Modulators of the Immune System and Neuroimmune System: Impact on the Host Health and Homeostasis. (22nd February 2015) - Maranduba, Carlos Magno da Costa; De Castro, Sandra Bertelli Ribeiro; Souza, Gustavo Torres de; Rossato, Cristiano; da Guia, Francisco Carlos; Valente, Maria Anete Santana; Rettore, João Vitor Paes; Maranduba, Claudinéia Pereira; Souza, Camila Maurmann de; Carmo, Antônio Márcio Resende do; Macedo, Gilson Costa; Silva, Fernando de Sá
Abstract : Many immune-based intestinal disorders, such as ulcerative colitis and Crohn's disease, as well as other illnesses, may have the intestines as an initial cause or aggravator in the development of diseases, even apparently not correlating directly to the intestine. Diabetes, obesity, multiple sclerosis, depression, and anxiety are examples of other illnesses discussed in the literature. In parallel, importance of the gut microbiota in intestinal homeostasis and immunologic conflict between tolerance towards commensal microorganisms and combat of pathogens is well known. Recent researches show that the immune system, when altered by the gut microbiota, influences the state in which these diseases are presented in the patient directly and indirectly. At the present moment, a considerable number of investigations about this subject have been performed and published. However, due to difficulties on correlating information, several speculations and hypotheses are generated. Thus, the present review aims at bringing together how these interactions work—gut microbiota, immune system, and their influence in the neuroimmune system.